2008
DOI: 10.1017/s1751731107001292
|View full text |Cite
|
Sign up to set email alerts
|

Effects of deep-bedded finishing system on market pig performance, composition and pork quality

Abstract: The purpose of this study was to compare effects of finishing environment on growth performance, pork quality and lipid composition of pork. Environments compared were standard confinement (CON) and deep-bedded semi-outdoor systems. The deep-bedded method employed in the current study was the use of hoop structures. Hoops are large, tent-like shelters with cornstalks or straw for bedding. Gilts ranging in weight from 59 to 71 kg were randomly assigned to treatments of Hoop (n 5 50) and CON (n 5 18) environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…In agreement with the present data, Patton et al (2008) found no effect of deep-bedded semi-outdoor housing compared with standard pig housing on pH1, pHu, colour, drip and cooking losses of pork. Accordingly, Millet et al (2005) concluded that indoor environmental enrichment or outdoor access for pigs had generally no impact on pork pH values.…”
Section: Meat Quality Indicatorssupporting
confidence: 92%
“…In agreement with the present data, Patton et al (2008) found no effect of deep-bedded semi-outdoor housing compared with standard pig housing on pH1, pHu, colour, drip and cooking losses of pork. Accordingly, Millet et al (2005) concluded that indoor environmental enrichment or outdoor access for pigs had generally no impact on pork pH values.…”
Section: Meat Quality Indicatorssupporting
confidence: 92%
“…In agreement, Duroc crossbreeds reared in A and C systems exhibited a similar carcass fatness (Lebret et al, 2011), whereas fatter carcasses and higher IMF content were found in synthetic line crossbred pigs produced in A compared with C housing system (Lebret et al, 2006). Contrasted results have also been reported regarding body fatness of pigs reared on bedding or offered larger space allocation, with either greater (Beattie et al, 2000;Gentry et al, 2002) or similar (Guy et al, 2002) carcass fatness and IMF content in alternative and conventional systems, whereas reduced back fat thickness and LM marbling score were found in pigs reared in deep bedding compared with conventional finishing system at similar stocking density (Patton et al, 2008).…”
Section: Pig Production Traits Were Mainly Affected By Breed and Extementioning
confidence: 87%
“…However, outdoor reared pigs weighed heavier on 140 days post-weaning. Different results were reported for gilts reared outdoors [ 17 ]. Given feed ad libitum , gilts had higher ADG and a higher feed efficiency (FE).…”
Section: Growth Performancementioning
confidence: 97%
“…The difference in the performance of the gilts compared to the performance of the pigs may be the result of difference in sex and experimental periods. Patton et al [ 17 ] assigned the gilts to treatments of either hoop or confinement at 4 months of age, at which their weights ranged from 59 to 71 kg, whereas the pigs in the study by Gentry et al [ 16 ] were kept in the study from weaning to 112 days post-weaning. Furthermore, the latter study was conducted in Lubbock, Texas, whereas the study by Patton et al was conducted in Ames, Iowa [ 16 , 17 ].…”
Section: Growth Performancementioning
confidence: 99%
See 1 more Smart Citation